Commercial milk formula feeding among children under two years in Nepal: Trends and determinants from four Nepal Demographic and Health Surveys (2006–2022) - Barun Kumar Singh; Sangita Bista; Sajjan Yogesh; Vishnu Khanal (PLoS ONE, 2026)
Background Exclusive breastfeeding in the first six months of life and continuation of breastfeeding until the second year are recommended for the healthy growth and development of infants and young children. However, the use of commercial milk formula has increased in recent decades in low and middle-income countries, including Nepal. Understanding the trends and determinants is crucial for designing evidence-based and context-specific infant and young child feeding support programs. There is limited evidence on the use of commercial milk formula in Nepal. Therefore, this study aimed to explore the trends and prevalence of commercial milk formula feeding practices and their associated factors among mothers of children aged 0–23 months in Nepal. Method We used data from four consecutive nationally representative surveys (2006, 2011, 2016, and 2022). A total weighted sample of 7,705 (0–5 months: 1,978; 6–23 months: 5,727) children aged 0–23 months was included in the analysis. The trends were presented as frequency distributions. Multivariable logistic regression was performed to assess the association between individual and underlying factors with commercial milk formula feeding in the first two years of life. For enhanced analytical clarity and programmatic relevance, we stratified our analysis into two distinct age groups: 0–5 months and 6–23 months. Results Over the study period (2006–2022), the prevalence of commercial milk formula feeding among infants aged 0–5 months increased steadily from 1.95% (95% confidence interval (CI): 0.83–4.55) to 11.09% (95% CI: 8.01–15.16). A similar but less upward trend was observed among children aged 6–23 months, with prevalence rising from 2.03% (95% CI: 1.26, 3.27) to 6.68% (95% CI: 5.26, 8.45). Among 0–5 months, infants born to mothers with secondary and higher education (adjusted odds ratio (aOR): 12.48; 95% CI: 2.63, 59.14), mothers aged 25–34 years (aOR: 2.29; 95% CI: 1.14, 4.60), and born by caesarean section (aOR: 2.16; 95% CI: 1.01, 4.59) were more likely to receive formula feeding compared to their counterparts. Similarly, among 6–23 months, children who were male (aOR: 1.67; 95% CI: 1.15, 2.42), perceived as small at birth (aOR: 2.76; 95% CI: 1.48, 5.15), first born (aOR: 2.59; 95% CI: 1.02, 6.56), born in health facilities (aOR: 3.18; 95% CI: 1.16, 8.73), and whose fathers had secondary or higher education (aOR: 3.14; 95% CI: 1.22, 8.10) were more likely to receive commercial milk formula. Conclusion The prevalence of commercial milk formula feeding practices has increased during 2006–2022. Evidence-informed, context-specific interventions are essential to halt and reverse commercial milk formula feeding practices and protect, promote, and support breastfeeding and recommended infant feeding practices. A program designed to address this issue should target vulnerable groups and leverage the specific factors identified in this study.